Analisis fungsi supervisi kepala ruangan dalam pengurangan risiko jatuh di Rumah Sakit X Jakarta: A pilot project - Agustina, Frima Ulfa; Afriani, Tuti; Handiyani, Hanny (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Falls is an incident that must be prevented when patients treated in the hospital. Nurses must comply withStandard Operating Procedures (SOP) to prevent the incidents of patient safety. Nursing supervision is oneway to improve nurse compliance. The method used is a pilot project by innovating. Implementation consistedof making drafting supervision work instructions, supervision instrument drafts, patient safety pocket books,innovation’s sosialization to 40 nurses consist of nursing services, nursing comitee, head nurses, head ofinstallations, leaders and associate nurses. The results of the study through the input project evaluation inthe form of interviews with 2 team leaders and 3 implementing nurses showed that headnurse’s instrumentsand work instructions supervision of falling risk reduction will help increase nurses' knowledge of StandardOperating Procedures (SOPs) for Falling Risk Reduction in Hospitals. Conclusion: the increase in nurses'knowledge about the reduction in fall risk is influenced by the supervisory function of the headnurse as thefirst-line nurse manager. Recommendation: this study is the basis for the implementation of supervision ofpatient safety targets, especially the reduction in the risk of falls.